Phrase Verbs in Minangkabau Language: X-Bar Theory - Tasya Angelita; Aini Nahdlia Puspita; F.X. Sawardi (Translation and Linguistics (Transling), 2025)
This research aims to describe the functional categories of interrogative words and formulate the structural rules for verb phrase constructions in Minangkabau language using the X-Bar theory. The research data consists of verb phrases in Minang language sourced from native Minang speakers. The research method employed is a qualitative, descriptive approach with data collection techniques involving participant observation followed by note-taking. The data is classified into categories that can combine with verb phrases in their construction. Subsequently, the data is analyzed and presented using an informal method for presenting the results of data analysis. Based on the data analysis, the study reveals findings related to the functional categories of verb phrase constructions in Minangkabau, namely complements and adjuncts. The adjunct function in verb phrase constructions is occupied by auxiliary constructions and the negation of 'not.' Meanwhile, the construction function as complements is occupied by the noun phrase constructions that attach to the verb phrase as patients subjected to the action.